Entropy analysis and thermal energy storage performance of PCM in honeycomb structure: Effects of materials and dimensions - Cihan, Ertugrul; Berent, Hasan Kaan; Demir, Hasan; Öztop, Hakan Fehmi (Elsevier, 2023)
This manuscript focuses on comprehensive investigation of entropy analysis and improve energy storage of phase change material (PCM) using a honeycomb material. In the last decade, the honeycomb structure has quickly emerged as a major tool for improving heat transfer rate, particularly for the back of solar radiation PV panels. The aim of this study was to investigate the effect of honeycomb cell wall thickness (0.2-2 mm), cell diameter (2-16 mm), and honeycomb material types (cellulose, graphite, polyethylene, stainless steel, magnesium alloy, aluminum, and copper) on heat transfer rate of paraffin. These parameters have significant impact on paraffin's energy storage. The variables were optimized numerically using the CFD techniques according to phase change behavior, kinetic energy storage, and total energy storage of composite/paraffin. The results showed that the embedded metal cage had no effect on the total heat storage capacity of paraffin (27.89 W) for 0.33 mm wall thickness of honeycomb. The other optimal geometrical specifications of a honeycomb were determined to be 10 mm cell diameter, and stainless-steel material. The ideal honeycomb cell has a uniform distribution of tem-perature and phase change in all cells at the same time. The entropy study confirmed that the phase transition of PCM with stainless steel honeycomb fins happened homogeneously and promptly. Furthermore, the heat transfer can be improved with changing the geometry of honeycomb structure, and addition fins inside cell.
Keywords: Honeycomb fin; Phase change material; Bejan number; Heat transfer in paraffin; Thermal energy storage